Ultrafast high-temperature synthesis and densification of high-entropy carbides. Issue 10 (August 2022) - Mao, Hai-Rong; Dong, Er-Ting; Jin, Shen-Bao; Qiu, Xiao-Ming; Shen, Ping
Abstract: Recently, high-entropy carbides have attracted great attention due to their remarkable component complexity and excellent properties. However, the high melting points and low self-diffusion coefficients of carbides lead to the difficulties in forming solid solution and sintering densification. In this work, six dense multicomponent carbides (containing 5–8 cations) were prepared by a novel ultrafast high-temperature sintering (UHS) technique within a full period of 6 min, and three of them formed a single-phase high-entropy solid solution. The solid solubility of the UHSed multicomponent carbides was highly sensitive to the compositional variation. The presence of Cr3 C2 liquid had significant contributions to the formation of solid solution and the densification of multicomponent carbides. All UHSed multicomponent carbides exhibited high hardness, which, unexpectedly, did not simply increase with increasing number of the components. The highest nanohardness with a value of 36.6 ± 1.5 GPa was achieved in the (Ti1/5 Cr1/5 Nb1/5 Ta1/5 V1/5 )C x high-entropy carbide. This work is expected to expedite the development of high-entropy carbides and broaden the application of UHS in the synthesis and densification of advanced ceramics. Graphical Abstract: ga1